The Awesome Adventures of Will and Randolph: The Last Dragon Hunter - Archer, Jeffrey (Saga Egmont, 2024)
Join brave boy Will, his chatty bear Randolph, and their trusty upside-down bird and get ready to leap into a world of magic and mystery! When a simple board game turns into a real-life adventure, the trio find themselves whisked away to Gravelburg town. Beware - there\'s more than meets the eye in this enchanting place. The dragon isn\'t what you\'d expect, and the brave knight might not be so heroic after all! From encounters with friendly dragons who love books more than treasure-hoarding to knights being turned into chickens, this tale is packed with laughs and surprises at every turn. When Will receives a mystical amulet, it brings his toy bear Randolph to life! This triggers a cascade of adventures where every book catapults them into peculiar new worlds. With Toy Story-like charm and Mr Benn\'s magical touch, this series follows their journey as they tackle moral dilemmas with courage and humour. Jeffrey Archer (1940-) is a bestselling British author and former politician, renowned for his captivating novels, short stories, and children\'s books published in over 97 countries and over 37 languages. His best-known works include ‘First Among Equals’, ‘Kane and Abel’ and ‘Only Time Will Tell’.